Formation of the Prosecution corps in Ukraine: current trends - Stefanchuk, Maryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article highlights the current trends in the formation of the prosecutor’s corps in Ukraine, caused by changes in the legislation on the selection and training of prosecutors. It has been established that one of the modern trends in the formation of the prosecutor’s corps in Ukraine is the simplification of the procedure for the selection and training of prosecutors to ensure the opportunity for a Law-school graduates to apply for the position of prosecutor. The questionable persuasiveness of this argument was noted, given the lack of such an opportunity for the positions of judges, lawyers, notaries, which is justified, considering the specifics of legal professions. The advantages of such changes are highlighted, as well as potential risks of successfully achieving the goal of improving the selection and training of prosecutors under the new legislation are noted. Among the advantages is the reduction of the selection period, which creates conditions for faster filling of vacant positions of prosecutors. Among the risks of successfully achieving the goal of improving the selection and training of prosecutors under the new legislation are the questionable expediency of involving trainee prosecutors into the group of prosecutors, as well as the absence of a legislatively established obligation of the internship supervisor to coordinate the trainee prosecutor’s decision regarding the procedural guidance of the pre-trial investigation in criminal proceedings. The ways to avoid such risks are suggested. In particular, to consider the working time costs of the intership superviser in carrying out the duty of approving decisions of the trainee-prosecutors as a separate component of such workload in the process of developing the procedure for measuring and regulating the workload on prosecutors, as well as establishing the trainee-prosecutor’s right to give formal feedback on the effecttiveness of the inernship superviser’s activities, which could be considered during the periodic evaluation of their work.